AB0786 Hand function and disability in patients with systemic sclerosis and digital ulcers. (23rd January 2014) - Nitsche, A.; Amitrano, C.; Pucci, P.; Lescano, A.
Abstract : Background: Digital ulcers (DU) affect hand function in patients with systemic sclerosis (SSc) causing pain and transient or permanent disability. In clinical practice, it is not clear which are the best and more sensitive questionnaires and tools to evaluate hand involvement in SSc DU patients. In the last two years 86 patients with SSc were evaluated, 46 of them had digital ulcers (DU).All our patients with DU had severe functional impairment of daily living activities, disability and poor life quality but this was not reflected in our medical records. Objectives: to evaluate the impact of DU in SSc patients by scoring: global disability by HAQ, pain by VAS, hand disability by the Cochin Hand Function Scale (CHFS) and functional mobility of the hand by modified Kapandji index (MKI). Methods: A transversal cohort study. 86 medical records of SSc patients were analyzed, 46 of them with DU and hand impairment. Because scoring this impairment was not routine in our practice, we evaluated only 14 of the 46 SSc DU patients. Hand function and disability were evaluated through VAS, HAQ, CHFS and MKI. VAS reflects pain in a scale from 0 to 100. HAQ evaluates global disability in musculoskeletal disorders: HAQ >1.25 is related to severe and active disease. CHFS questionnaire consists of 18 questions (scored each from 0 to 5; total score 90) aiming to assess daily hands activities. MKI index evaluates wrist, opposition of the thumb and flexo-extension of the rest of the fingers (score 0 – 100 for both hands). Results: 14 patients were evaluated;13 female; mean age of 55±10.16 years; mean evolution time of SSc 7±6.5 years. Diffuse SSc (dSSC) was diagnosed in 5 (36%) patients and limited (lSSc) in 9 (64%). In the 14 patients we analyzed three different status of DU: healed, active and with digital tissue loss. Seven patients (50%) had a combination of DU lesions. For the 14 patients, irrespectively of the DU status, the mean value of HAQ was 1.45; VAS of 4, 76, Cochin score with a mean value of 25 and the total mean value of Kapandji index was 81. These data reflects that impairment of the hand function (HAQ, CHFS and MKI) had a greater impact than pain (VAS) in our patients. Conclusions: We found no difference between DU different status: pain and disability in daily activities were present in all three groups. Impairment had more impact in hand function than in pain scores. HAQ, CHFS, VAS and MKI as part of our clinical practice in SSc patients are useful tools to decide pharmacologic and non- pharmacologic treatment options. References: Influences of clinical features of systemic sclerosis on the Michigan Hand Questionnaire (MHQ) Impens AJ et al Arthritis 2006; 54: S 483. Digital ulcers and outcomes assessment in sclerodema. Matucci-Cerinic M et al Rheumatology 2008; 47: 46-47. Using a self-reported functional store to asses disease progresiόn in systemic slerosis. Serednicka K et al Rheumatology 2007; 46: 1107-10 Assessing disability and Quality of life in Systemic sclerosis: construct validities of the Cochin Hand function scale, Health Assessment Questionnaire, Systemic sclerosis HAQ and Medical outcomes Study 36-Item Short Form Health Survey. Rannou F et al Arthritis 2007, 57: 94-102. Disclosure of Interest: None Declared